Relationship of Contextual Cueing and Hippocampal Volume in Amnestic Mild Cognitive Impairment Patients and Cognitively Normal Older Adults. (20th May 2015) - Negash, Selam; Kliot, Daria; Howard, Darlene V.; Howard, James H.; Das, Sandhistu R.; Yushkevich, Paul A.; Pluta, John B.; Arnold, Steven E.; Wolk, David A.
Abstract: There is currently some debate as to whether hippocampus mediates contextual cueing. In the present study, we examined contextual cueing in patients diagnosed with mild cognitive impairment (MCI) and healthy older adults, with the main goal of investigating the role of hippocampus in this form of learning. Amnestic MCI (aMCI) patients and healthy controls completed the contextual cueing task, in which they were asked to search for a target (a horizontal T) in an array of distractors (rotated L's). Unbeknownst to them, the spatial arrangement of elements on some displays was repeated thus making the configuration a contextual cue to the location of the target. In contrast, the configuration for novel displays was generated randomly on each trial. The difference in response times between repeated and novel configurations served as a measure of contextual learning. aMCI patients, as a group, were able to learn spatial contextual cues as well as healthy older adults. However, better learning on this task was associated with higher hippocampal volume, particularly in right hemisphere. Furthermore, contextual cueing performance was significantly associated with hippocampal volume, even after controlling for age and MCI status. These findings support the role of the hippocampus in learning of spatial contexts, and also suggest that the contextual cueing paradigm can be useful in detecting neuropathological changes associated with the hippocampus. ( JINS, 2015, 21, 285–296)